2007
DOI: 10.1677/erc.1.01253
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of human salivary gland tumor cells by introduction of progesterone (Pg) receptor and Pg treatment

Abstract: Cancer of the salivary gland is one of the common cancers in the head and the neck regions. This type of cancer develops in the minor and the major salivary glands, and it sometimes metastasizes to other organs, particularly the lung. Morphologic mimicry and similarity in the expression of steroid hormone receptors between salivary gland tumors (SGTs) and breast tumors are well-known phenomena and are occasionally debated in the field of surgical pathology. Progesterone (Pg), one of the female sex steroid horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…We previously reported that aggressiveness was reduced in PR-deficient human aggressive breast cancer cells after PR was reintroduced and treated with Pg [20]. Further, we found that Pg could act as an inhibitor of SGC cell proliferation [13]. In these two studies, we reported that progesterone-induced growth inhibition was accompanied by both up-regulation of p21, which generally plays a critical role in regulating cell growth inhibition [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that aggressiveness was reduced in PR-deficient human aggressive breast cancer cells after PR was reintroduced and treated with Pg [20]. Further, we found that Pg could act as an inhibitor of SGC cell proliferation [13]. In these two studies, we reported that progesterone-induced growth inhibition was accompanied by both up-regulation of p21, which generally plays a critical role in regulating cell growth inhibition [13].…”
Section: Discussionmentioning
confidence: 99%
“…Pooled cell populations of PR-expressing cells were prepared as previously described [13]. Briefly, a pSG5 plasmid was used to introduce vectors hPR1 and hPR2, which contained human PR cDNA coding for isoforms PR-B and PR-A, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Specifically, we demonstrated that after transduction of PR, progesterone could significantly suppress the proliferation (and invasion) of MSGT cells (Yoshimura et al, 2007). This suppression did not lead to cell death, but instead to cell cycle arrest.…”
mentioning
confidence: 81%
“…Although a number of studies have been published, the rationale for hormone therapy of MSGTs remains controversial because of disparate results and an insufficient number of cases. However, some recent studies have shown that certain salivary gland neoplasms are similar to breast cancer, not only in terms of their pathological features, but also at the molecular level (Pia-Foschini, 2003;Wick et al, 1998;Yoshimura et al, 2007). Here, we shed light on the biological similarity between MSGTs and certain types of breast cancer, and describe the potential use of hormone and additional therapies for MSGTs.…”
Section: Introductionmentioning
confidence: 87%